Integration of Islamic Social Finance and Digitalization for MSME Strengthening and Poverty Alleviation: Evidence from SEM-PLS - Danil Syahputra; Supiah Ningsih; Muhammad Radian Syah (Journal of Economics, Entrepreneurship, Management Business and Accounting, 2026)
Purpose - This study examines the integrated role of Islamic social finance and economic digitalization in strengthening MSMEs and alleviating poverty in North Sumatra, Indonesia. While prior studies have largely analyzed these domains separately, this research is motivated by the need for a unified framework that explains how their interaction contributes to inclusive economic development. The study specifically investigates the mediating role of MSME strengthening in linking finance digitalization integration to poverty reduction. Design/Methodology/Approach – A quantitative explanatory approach was employed using survey data from 210 MSMEs across trade, service, and food processing sectors. Data were analyzed using Partial Least Squares Structural Equation Modeling (SEM-PLS) with bootstrapping (5,000 resamples) to test direct and indirect relationships among Islamic social finance integration, economic digitalization, MSME strengthening, and poverty alleviation. Findings/Results - The results show that Islamic social finance integration (β = 0.312) and economic digitalization (β = 0.421) significantly enhance MSME strengthening. Both variables also directly influence poverty alleviation (β = 0.198 and β = 0.243), while MSME strengthening has a strong positive effect on poverty alleviation (β = 0.379). Mediation analysis confirms that MSME strengthening partially mediates these relationships, indicating that MSMEs function as a key transmission mechanism. These findings demonstrate that integrating financial inclusion and digital transformation produces both direct and indirect welfare effects. Originality/Value - This study contributes by proposing an integrated finance digitalization framework that positions MSMEs as a central mediating mechanism in poverty alleviation. The findings highlight that sustainable poverty reduction is more effective when Islamic social finance is combined with digital economic systems and channeled through MSME development, offering practical implications for policymakers in designing inclusive, technology-enabled economic strategies.